DNA vaccines encoding DEC205‐targeted antigens: immunity or tolerance?. Issue 4 (30th April 2015) - Niezold, Thomas; Storcksdieck genannt Bonsmann, Michael; Maaske, André; Temchura, Vladimir; Heinecke, Vanessa; Hannaman, Drew; Buer, Jan; Ehrhardt, Christina; Hansen, Wiebke; Überla, Klaus; Tenbusch, Matthias
Summary Targeting of antigens to the endocytic uptake receptor DEC205 resulted in enhanced antigen presentation by dendritic cells (DCs). In combination with adjuvants for DC maturation, proteins coupled to an antibody against DEC205 induced strong pathogen‐specific immune responses, whereas without additional adjuvant tolerance could be induced. As less is known about DNA vaccines encoding DEC205‐targeted antigens, we explored the immunogenicity and efficacy of a dendritic cell‐targeted DNA vaccine against influenza A virus (IAV) delivered by electroporation. Although coupling of haemagglutinin to a single‐chain antibody against DEC205 enhanced antigen presentation on MHC class II and activation of T‐cell receptor‐transgenic CD4 T cells, the T‐cell responses induced by the targeted DNA vaccine in wild‐type BALB/c mice were significantly reduced compared with DNA encoding non‐targeted antigens. Consistently, these mice were less protected against an IAV infection. Adoptive transfer experiments were performed to assess the fate of the antigen‐specific T cells in animals vaccinated with DNA encoding DEC205‐targeted antigens. By this, we could exclude the general deletion of antigen‐specific T cells as cause for the reduced efficacy, but observed a local expansion of antigen‐specific regulatory T cells, which could suppress the activation of effector cells. In conclusion, DNA vaccines encoding DEC205‐targeted antigens induce peripheral tolerance rather than immunity in our study. Finally, we evaluated our DNA vaccines as prophylactic or therapeutic treatment in an allergen‐induced asthma mouse model.